Current status of pediatric deceased donor liver transplantation: Lessons learned from a high‐volume center in Japan where living donation remains predominant. (30th December 2020) - Sakamoto, Seisuke; Uchida, Hajime; Shimizu, Seiichi; Yanagi, Yusuke; Takeda, Masahiro; Kubota, Tomomi; Nakazato, Yayoi; Fukuda, Akinari; Kasahara, Mureo
Abstract: Background: In Japan, a recent gradual increase in deceased donor donation has expanded opportunities for pediatric patients to obtain deceased grafts. Methods: Forty‐three children underwent deceased donor liver transplantation (DDLT) at our institute before February 2020. Twenty‐five patients received a split or reduced graft and 18 patients received a whole graft. The clinical outcomes of DDLT were retrospectively analyzed. Results: The main organ resource was split/reduced grafts retrieved from adult donors; however, the number of whole grafts retrieved from pediatric donors has increased. The rates of major complications were similar in the two groups. The 5‐year graft survival rate of patients who received a split/reduced graft (78.0%) was lower than that of patients who received a whole graft (88.9%; P  = .40). The 3‐year graft survival rates of patients who recently received a split/reduced graft and a whole graft improved to 92.3% and 91.7%, respectively. Conclusions: The recent amendment of the organ allocation system, especially the introduction of pediatric prioritization, can effectively increase the chance to obtain deceased donor grafts for pediatric DDLT in Japan. The recent refinements in donor and recipient selection and in the surgical technique of split DDLT can improve the outcomes of pediatric DDLT in Japan. Abstract : Highlight Sakamoto and colleagues retrospectively analyzed pediatric deceased donor liver transplantation (DDLT) at Japan's largest pediatric liver transplant center. Pediatric prioritization has increased the chance to obtain deceased donor grafts, and refinements in donor and recipient selection and in the split DDLT technique can improve the outcomes of pediatric DDLT in Japan.